PENGARUH VIRTUAL REALITY MILLEALAB UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI KELAS IV PADA MATA PELAJARAN KEWARGANEGARAAN - Mochamad Faridz; Dhea Adela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Virtual Reality (VR) Millealab application on increasing the learning interest of fourth-grade students in Civics Education (PKn). A quantitative approach with a quasi-experimental method and a nonequivalent control group design was used, involving 30 fourth-grade students of SD Negeri 3 Nyalindung, divided into an experimental group (VR Millealab, n = 15) and a control group (conventional PowerPoint, n = 15). Learning interest was measured using a 22-item Likert questionnaire developed from Keller’s ARCS model and administered as a pretest and posttest. Data were analysed using JASP through descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, an independent samples t-test on N-Gain scores, and a supporting mixed ANOVA. The results showed that the pretest scores of both groups did not differ significantly (t = 0.57; p = .57), confirming baseline equivalence. After the treatment, the experimental group’s N-Gain (M = 0.57, medium category) was significantly higher than the control group’s (M = 0.25, low category), t(28) = 3.62, p = .001, Cohen’s d = 1.32, and this was reinforced by a significant Time × Group interaction in the mixed ANOVA, F(1, 28) = 6.48, p = .02. These findings indicate that VR Millealab has a significant effect on increasing students’ interest in learning Civics Education and can be considered as an innovative alternative instructional medium at the elementary school level.